Opposite Effects of the S4–S5 Linker and PIP2 on Voltage-Gated Channel Function: KCNQ1/KCNE1 and Other Channels - Choveau, Frank S.; Abderemane-Ali, Fayal; Coyan, Fabien C.; Es-Salah-Lamoureux, Zeineb; Baro, Isabelle; Loussouarn, Gildas (Frontiers in Pharmacology, 2012)
Voltage-gated potassium (Kv) channels are tetramers, each subunit presenting six transmembrane segments (S1-S6), with each S1-S4 segments forming a voltage-sensing domain (VSD) and the four S5-S6 forming both the conduction pathway and its gate. S4 segments control the opening of the intracellular activation gate in response to changes in membrane potential. Crystal structures of several voltage-gated ion channels in combination with biophysical and mutagenesis studies highlighted the critical role of the S4-S5 linker (S4S5L) and of the S6 C-terminal part (S6T) in the coupling between the VSD and the activation gate. Several mechanisms have been proposed to describe the coupling at a molecular scale. This review summarizes the mechanisms suggested for various voltage-gated ion channels, including a mechanism that we described for KCNQ1, in which S4S5L is acting like a ligand binding to S6T to stabilize the channel in a closed state. As discussed in this review, this mechanism may explain the reverse response to depolarization in HCN-like channels. As opposed to S4S5L, the phosphoinositide, phosphatidylinositol 4,5-bisphosphate (PIP2), stabilizes KCNQ1 channel in an open state. Many other ion channels (not only voltage-gated) require PIP2 to function properly, confirming its crucial importance as an ion channel co-factor. This is highlighted in cases in which an altered regulation of ion channels by PIP2 leads to channelopathies, as observed for KCNQ1. This review summarizes the state of the art on the two regulatory mechanisms that are critical for KCNQ1 and other voltage-gated channels function (PIP2 and S4-S5L), and assesses their potential physiological and pathophysiological roles.